Phytoplankton Impact on Marine Cloud Microphysical Properties Over the Northeast Atlantic Ocean. Issue 10 (24th May 2022) - Mansour, Karam; Rinaldi, Matteo; Preißler, Jana; Decesari, Stefano; Ovadnevaite, Jurgita; Ceburnis, Darius; Paglione, Marco; Facchini, Maria C.; O'Dowd, Colin
Abstract: The current understanding of the impact of natural cloud condensation nuclei (CCN) variability on cloud properties in marine air is low, thus contributing to climate prediction uncertainty. By analyzing cloud remote sensing observations (2009–2015) at Mace Head (west coast of Ireland), we show the oceanic biota impact on the microphysical properties of stratiform clouds over the Northeast Atlantic Ocean. During spring to summer (seasons of enhanced oceanic biological activity), clouds typically host a higher number of smaller droplets resulting from increased aerosol number concentration in the CCN relevant‐size range. The induced increase in cloud droplet number concentration (+100%) and decrease in their radius (−14%) are comparable in magnitude to that generated by the advection of anthropogenically influenced air masses over the background marine boundary layer. Cloud water content and albedo respond to marine CCN perturbations with positive adjustments, making clouds brighter as the number of droplets increases. Cloud susceptibility to marine aerosols overlaps with a large variability of cloud macrophysical and optical properties primarily affected by the meteorological conditions. The above findings suggest the existence of a potential feedback mechanism between marine biota and the marine cloud‐climate system. Plain Language Summary: Marine phytoplankton contributes to the natural aerosol burden in the atmosphere. Aerosol particles serve as cloud condensation nuclei that play an important role in cloud formation. Clouds cool the earth's surface by scattering and reflecting the incoming solar radiation to space. We found that the enhancement of oceanic biological activity during spring and summer times leads to an increase in the number of droplets in stratiform clouds, over the Northeast Atlantic Ocean, and a decrease in their size. This happens as a consequence of the higher aerosol concentrations resulting from enhanced marine biogenic emissions. The magnitude of changes in cloud microphysical parameters caused by contrasting marine biota conditions is comparable to that observed by comparing anthropogenically influenced and background marine air masses. Furthermore, we observed that cloud brightness responds positively to marine aerosol sources ( i.e., clouds are brighter as the number of droplets increases), even though this relationship is non‐linear. These results are important for understanding the causes of variability in cloud radiative effects and for the improvement of climate predictions. Key Points: Ground‐based observations show variations in cloud droplet number (+100%) and their radius (−14%) associated with high phytoplankton activity The biota‐induced variations in stratiform cloud microphysics are comparable in magnitude to those generated by anthropogenic inputs Cloud optical properties mainly respond to meteorology, however, the increase in summer droplet number contributes to enhanced albedo